Carisma e realidade do General Francisco da Silveira : um militar de carreira em momento de viragem - Serén, Maria do Carmo (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The Count of Amarante, who was responsible for many military victories against the French troops, is regarded as one of the figures responsible for reinstating John of Portugal as the Prince Regent, for preventing Loison and Soult join their regiments, allowing Wellesley’s attack to Porto and, as commander in chief of the Portuguese and British troops, and to force out the French forces through a series of battles in Spanish territory. For his military victories he was awarded the Victory Medal together with Wellington. However, contrary to the British strategy to conquer Lisbon, his conception of population defence reveals his ability to resist by organizing an army based on single volunteers, groups of militia and guerrilla forces. It also confirms the role played by the Portuguese military capacity to defeat Napoleon’s army and, to some extent, contributes to understand its inner contradictions during the 1820’s revolution.